The effects of fatiguing exercise and load carriage on the perception and initiation of movement - Johnson, C. D.; Eagle, S. R.; Nindl, B. C.; Lovalekar, M. T.; Flanagan, S. D.; Pepping, G.-J. (European Journal of Sport Science, 2021)
Perceptual-motor coordination relies on the accurate coupling of the perceptual and movement systems. However, individuals must also be able to recalibrate to perturbations to perceptual and movement capabilities. We examined the effects of fatigue and load carriage on perceptual-motor coordination for a maximal leaping task. 23 participants completed an incremental fatigue protocol (light to fatiguing intensity stages) on two separate occasions (loaded/unloaded). At baseline and the end of every stage of the protocol, participants made perceptual judgments for the affordance of leaping. The accuracy of responses and reaction times were calculated. Mean differences in accuracy and reaction time across exercise intensity and load carriage conditions. No interaction of exercise intensity and load carriage was detected, or main effect of load carriage. A main, quadratic effect of exercise intensity was detected on reaction, with times decreasing through the moderate stage and increasing through post-fatigue. No effect of exercise/fatigue was detected on perceptual accuracy. The results indicate that exercise at high intensities through fatigue have a significant effect on perceptual-motor calibration. Contrastingly, in response to an action-scaled task, individuals can adequately recalibrate to increased load carriage.